2013
DOI: 10.1093/carcin/bgt161
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ASPP2 in choriocarcinoma contributes to increased migratory potential through Src signaling pathway activation

Abstract: Gestational choriocarcinoma is a malignant tumor derived from placental trophoblast and the most aggressive member of gestational trophoblastic disease (GTD). Apoptosis-stimulating protein of p53-2 (ASPP2) is a member of ASPP family that transactivates p53 and thereby functions as a tumor suppressor. In this study, the expression profile of ASPP2 in choriocarcinoma was examined in comparison with normal placentas and hydatidiform moles, the latter being a type of GTD that carries malignant potential. Downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…ASPP2 is commonly considered a tumor suppressor, and its expression is often reduced in malignant tumors [14, 24, 25]. However, inconsistent with previous reports, our results indicated that ASPP2 expression was significantly increased in ESCCs as compared with noncancerous tissues, suggesting that ASPP2 might be involved in ESCC tumorigenesis.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…ASPP2 is commonly considered a tumor suppressor, and its expression is often reduced in malignant tumors [14, 24, 25]. However, inconsistent with previous reports, our results indicated that ASPP2 expression was significantly increased in ESCCs as compared with noncancerous tissues, suggesting that ASPP2 might be involved in ESCC tumorigenesis.…”
Section: Discussioncontrasting
confidence: 93%
“…Iwabuchi et al [43] suggested that ASPP1 and ASPP2 exerted their function of inhibiting tumorigenesis only in the presence of wild-type P53. However, later studies showed that ASPP2 played tumor-suppressing roles independent of P53, such as enhancing colorectal cancer cell apoptosis through autophagy inhibition [18], inhibiting cell migration through Src inactivation [14], and stimulating Ras-induced senescence through direct interactions with Ras-GTP [44]. Additionally, we did not find any correlation among ASPP1, ASPP2, and P53, indicating that they may all function independently.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, we have previously demonstrated that proapoptotic apoptosisstimulating protein of p53 2 is down-regulated in highly metastatic CCA and contributes to increased migratory potential through the activation of the Src signaling pathway. 11 Interestingly, our qPCR analysis of apoptotic genes in FBI1etransfected CCA cells revealed an unreported downregulation of a broad range of proapoptotic genes in both intrinsic and extrinsic pathways, including death receptor FAS, apoptosis-initiating BAK, initiator caspases (CASP8, CASP9, and CASP10), as well as apoptosis-executing polyeADP ribose polymerases ( Figure 5). FBI-1einduced down-regulation of these proapoptotic gene transcripts implicates the ability of FBI-1 to manipulate apoptosis cassette/machineries and to hence protect cells from apoptosis in GTD.…”
Section: Discussionmentioning
confidence: 91%
“…15 In GTD, p53-related genes or regulators play crucial roles in modulating apoptosis during disease progression. 9,11 Also, the involvement of these regulators in crosstalk between apoptosis and the cell signaling pathway in GTD may result in an adverse clinical outcome. For example, we have previously demonstrated that proapoptotic apoptosisstimulating protein of p53 2 is down-regulated in highly metastatic CCA and contributes to increased migratory potential through the activation of the Src signaling pathway.…”
Section: Discussionmentioning
confidence: 99%